PoSiF: A Transient Content Caching and Replacement Scheme for ICN-IoT - Dhawan, Geetu; Mazumdar, Arka P.; Meena, Yogesh K. (Wireless Communications and Mobile Computing, 2023)
Efficient data management plays a critical role in facilitating smooth communication and optimizing resource utilization within the rapidly growing ecosystem of the internet of things (IoT), which creates vast amounts of content. The emergence of Information-Centric Networking (ICN) has positioned it as a promising paradigm for facilitating IoT applications, as it prioritizes content-centric communication. This inherent characteristic of ICN has the potential to greatly improve the performance of IoT systems through the reduction of latency, conservation of network capacity, and enhancement of scalability. Existing research in this area focuses primarily on the popularity and freshness of the contents. However, they overlook the limited cache size of constraint devices, which should be utilized efficiently. This article presents a popularity, size, and freshness-based (PoSiF) transient content caching, and cache replacement scheme for ICN-enabled IoT devices. For content placement and replacement, the PoSiF scheme aims to enhance cache utilization through these three parameters while addressing the tradeoff between content size and popularity. The PoSiF technique demonstrates a significant enhancement in cache hit rates, with an improvement of 21.6% compared to the existing CCS/CES scheme, while effectively reducing hop ratios by 42.5%. On the other hand, cache replacement observes improved cache hits of 18% over least recently used (LRU) and 7.2% over least frequently used (LFU) while decreasing the average distance by 4.1% and 7.2%, respectively. While the retrieved freshness is 8.12% and 3.2% less than the LRU and LFU schemes, PoSiF compensates by satisfying more queries from cache-based content storage than the alternative methods.